In vivo test of Litopenaeus vannamei infected by Vibrio using Moringa oleifera leaf extract - Iko Imelda Arisa; Cut Mutia; Sri Agustina; Nurfadillah Nurfadillah; Sofyatuddin Karina (Depik, 2021)
This study aimed to determine the optimal concentration of Moringa oleifera leaf extract as an antibacterial agent on Litopenaeus vannamei larvae that are infected by Vibrio sp.. It was conducted in 15 March - 15 April 2019 at PT. Global Gain Superior Seeds, Pantai Cermin, North Sumatera. The research used a completely randomized design (CRD) method with five treatments and four replications. The shrimps infected by Vibrio sp. were immersed into M. oleifera leaf extract in various concentration of (A) 0 ppm, (B) 400 ppm, (C) 600 ppm, (D) 800 ppm, and (E) 1000 ppm for 15 minutes. The size of shrimp used was post-larvae 8 (length of 3.5-5 mm/ind). The best performance results of vannamei shrimps were obtained in treatment E (1000 ppm), namely length growth of 16.75 1.16 cm, weight growth of 0.92 0.89 g and survival rate of 917.87%.Keywords:Moringa oleiferaVibrio sp.Immersion